Association between olfactory dysfunction and gustatory dysfunction: evidence from the National Health and Nutrition Examination Survey - Yang, Yi; Zhang, Chao; Xiong, Tao (Frontiers in Public Health, 2025)
BackgroundOlfactory dysfunction (OD) and gustatory dysfunction (GD) are common among adults, with prevalence increasing significantly in older age groups. Both dysfunctions have negative effects on appetite, nutrition, social functioning and even environmental safety. OD and GD frequently coexist, indicating a possible close association between these conditions. At present, there is a lack of large-sample epidemiological studies on the relationship between OD and GD. Our study aims to investigate the relationship between OD and GD using both measurement and questionnaire data from the 2013–2014 NHANES for US adults aged 40 years and older.MethodsThis cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES). OD and GD were both assessed by measurements and questionnaires. The association between OD and GD was investigated with logistic regression models by adjusting for demographic characteristics, systemic diseases, and diseases of the nose and pharynx. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) are presented.ResultsParticipants with complete olfactory and gustatory measurements and questionnaires (n = 2,582) were included. Using whole-mouth measurements, anosmia OD significantly increased the odds of hypogeusia and ageusia GD after adjusting for confounding factors. Similarly, the questionnaire data revealed that OD significantly increased the odds of GD. However, hyposmia OD decreased the odds of hypogeusia GD using the tongue-tip taste measurement.ConclusionOur findings highlighted that OD was closely associated with GD in a nationally representative sample of US adults.